PEROLEHAN KEMBALI PERAK DARI LIMBAH SISA ANALISIS COD MENGGUNAKAN METODA ELEKTROLISIS - Djaenudin Djaenudin; Mindriany Syafila (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2009)
The spent COD test solution has unique characteristics, i.e. small in volume and discontinued in production. However, it contains hazardous elements to environment such as heavy metals, i.e. silver, mercury, iron, and chromium, which could be having an economic value if can be reused. This research was subjected to the recovery of silver element the spent COD test solution using electrolysis method. The anode used was made from platinum sized 1 x 1 cm2, whereas copper was used as the cathode. The optimum silver recovery using the artificial waste of Ag2SO4 was 19.93% and the reaction rate constant value (k) was 0.0363 /minute from initial silver concentration of 199.375 mg/L to became 159.64 mg/L. This result was obtained on the experimental conditions of 5 cm electrode distance, 1 x 3 cm2 cathode surface area and DC supply voltage of 6 volt. The experiment using the spent COD test solution was carried out at electrode distance of 5 cm, cathode surface area of 1 x 3 cm2 and DC supply voltage of 6 volts. The silver recovery was 47.19% from initial silver concentration of 204.375 mg/L to be 107.92 mg/L and the reaction rate constant value (k) was 0.1053 /minute. The results showed that the increasing in DC supply voltage and the reducing in the electrode distance would increase the silver recovery.